The microbiome and chronic rhinosinusitis - Rahuram Sivasubramaniam (KeAi Communications Co., Ltd., 2018)
Chronic rhinosinusitis (CRS) is a multifactorial condition in which the microbiota plays a pathogenic role. The nature of the interaction between the microbiota and the local immune system is very complex and has not been fully elucidated. Recent improvements in the microbiological techniques have greatly advanced our understanding of the complex nature of this interaction. This paper summarizes the current state of the rapidly evolving research on this subject. Defining the nature of the role of the microbiota in CRS is important because of the associated therapeutic implications. Keywords: Sinusitis, Microbiome, Bacteriology, Polyposis, Pathogenesis, Inflammation